(untitled) (Malaysian Journal of Learning and Instruction, 2019)
Purpose - Recently, a layered and lateral framework that provides opportunities for students to design the pedagogy that creates a broad based, flexible and personalized learning is introduced by the Taylor’s University School of Engineering. This approach creates avenue for the students to design their own curriculum within the framework that is developed with inputs from the industry. The framework, the key components, and the tracking of the performance to align the set outcomes through assessment tool is presented. Methodology - My Study Plan (MySP) a macro-enabled software is used to develop a four-year tier model for the students to design the curriculum with the help of a mentor at the start of the programme. Student’s learning is monitored on a semester-based learning analytics process implementing the Programme Outcomes (PO) Scorecard. The August 2018 cohort of the Electrical and Electronic Engineering programme is used to pilot this pedagogy. Findings - Currently the PO measurement is done for the graduating student and focus only on the effectiveness of the programme. The Programme Outcome Assessment Review (POAS) used in this study to monitor the MySP the continual monitoring each semester rather towards the end of graduation. Initial simulation of existing PO attainment record of students suggest that this can generate interest towards the learning progress on a semester basis. Significance - The successful adoption sees an effectiveness in the long run in developing graduates through the continual monitoring of the programme outcomes. The graduating students carry the PO scorecard that complements a second transcript for value addition for their studies. Prospective employers can use the PO scorecard as a metric for initial recruitment purposes, a measure for the soft skills achievements of the applicant.